(untitled) (Nordic Journal of African Studies, 2003)
This paper examined the management of conflicts in the administration of secondary schools in Osun State, Nigeria. It also identified, discussed and analysed the causes as well as the various ways conflicts manifested in the administration of secondary schools in the state. The effects of conflicts on school administration were equally examined. Quantitative and qualitative data were generated from both primary and secondary sources. The paper showed that administration of secondary schools in the state was hampered by high rate of conflicts. Several types of conflicts were identified in the schools among which were conflicts between management and staff; between staff and students; between the communities and schools; and inter-personal conflicts to mention a few. The causes of conflicts in schools in the state included inadequate welfare package for workers; forceful and compulsory retirement/retrenchment of workers; administrative incompetence; personality clashes; role conflicts; and non-involvement of students in school administration. The fact that most of the school administrators were not knowledgeable in conflict management, coupled with the absence of laid down procedures for conflict management in most schools contributed to the high rate of conflicts and industrial actions in the schools. The paper concluded that the issue of conflict management in school administration has reached a point where effective use of relevant strategies can no longer be ignored.